ANALYZING HOUSEHOLD DEMAND FOR ANIMAL FOOD AS A SOURCE OF PROTEIN: THE CASE OF RURAL GORONTALO PROVINCE, INDONESIA - Nikmatul Khoiriyah; Hadi Apriliawan; David Forgenie (Socio-Economics/Agribusiness Department, 2023)
Animal foods are a major source of protein for households. Gorontalo Province has a lot of potential for marine fishery development, despite being one of the provinces where families consume less protein than the national protein sufficiency rate. This article investigates the household elasticity of demand for animal food in the context of increasing prices and incomes. The Quadratic Almost Ideal Demand System is used in to estimate the share equations from which reliable price and income elasticities can be derived. The article utilizes secondary data from the National Socio-Economic Survey for March 2021, which includes consumption and household expenditure information on all animal protein-containing meals, 4,811 households make up the study's sample. All animal foods, except for eggs, were found to be highly price elastic. The most elastic food is beef, which has a demand elasticity of 3.829%, followed by chicken meat (3.13%), fish (2.345%), milk (1.311%), and eggs (0.846 percent). Eggs were discovered to be price inelastic. Except for eggs, all animal products are considered luxury goods as indicated by income elasticity estimates. Beef has the highest income elasticity (3.181%), followed by chicken (2.957%), fish (1.674%), and milk (1.574 percent). Eggs are normal items because their income elasticity is the lowest at 0.589 percent. This finding confirms that for households in rural Gorontalo, price policy is more effective than income policy.